(untitled) (Research, Society and Development, 2021)
In molecular phylogeny of Malpighiaceae, the Ptilochaetoide clade is composed of Dinemagonum, Dinemandra, Lasiocarpus and Ptilochaeta, found in the sub-desert and desert regions of South and Central America. The taxonomic relationship between the genera of the group is little discussed and phylogenetic studies point out to the need for an evolutionary approach using morphoanatomical characters. Thus, based on the recurrent contribution of leaf anatomy to taxonomic studies in Malpighiaceae, we characterized the leaf anatomy of seven species of the Ptilochaetoide clade and listed relevant anatomical patterns for their circumscription. For this, we used standard anatomical techniques and the anatomical data were discussed phylogenetically. The anatomical data such as: petiole/midrib contour, petiole/midrib vascular system conformation, presence/absence of trichomes and mesophyll organization were useful for the elaboration of the identification key. Character states: Plane-convex midrib contour, isobilateral mesophyll and absence of trichomes were considered informative for the subclade composed by Dinemandra and Dinemagonum, while in the other genera, no relevant morphotypes were recognized. The absence of accessory bundles, presence of druses and sheath extension are common features in the clade and contribute to the group description. These findings reaffirm the effectiveness of leaf anatomy in taxonomic and phylogenetic studies in Malpighiaceae.